2002
DOI: 10.1152/jn.2002.87.5.2237
|View full text |Cite
|
Sign up to set email alerts
|

Neural Representations of Sinusoidal Amplitude and Frequency Modulations in the Primary Auditory Cortex of Awake Primates

Abstract: We investigated neural coding of sinusoidally modulated tones (sAM and sFM) in the primary auditory cortex (A1) of awake marmoset monkeys, demonstrating that there are systematic cortical representations of embedded temporal features that are based on both average discharge rate and stimulus-synchronized discharge patterns. The rate-representation appears to be coded alongside the stimulus-synchronized discharges, such that the auditory cortex has access to both rate and temporal representations of the stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
266
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(301 citation statements)
references
References 45 publications
30
266
2
Order By: Relevance
“…This response to low-frequency signals and envelopes of high-frequency narrowband signals can be thought of as another form of cue invariance, except in this case, it pertains to sound localization, not object perception. Observations of independence between optimal carrier and envelope frequencies in the auditory cortex also support the idea of parallel transmission of signal and envelope (29,31,32).…”
Section: Discussionsupporting
confidence: 53%
“…This response to low-frequency signals and envelopes of high-frequency narrowband signals can be thought of as another form of cue invariance, except in this case, it pertains to sound localization, not object perception. Observations of independence between optimal carrier and envelope frequencies in the auditory cortex also support the idea of parallel transmission of signal and envelope (29,31,32).…”
Section: Discussionsupporting
confidence: 53%
“…However, Lu et al (2001) showed that a distinct population of neurons exists in the auditory cortex of marmosets that encodes highmodulation frequencies as a rate code. A rate code for highmodulation frequencies in the auditory cortex was also reported in other studies (Bieser and Muller-Preuss, 1996;Liang et al, 2002;Lu and Wang, 2004). Our current results suggest that neurons in the auditory cortex of P. discolor represent IR roughness as a rate code.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that anesthesia has been shown to affect the cortical response to successive stimuli (16,17). However, anesthesia would not create a bias in estimations made in PN-exposed versus naïve rats because of identical anesthetic conditions during recording for both rat groups.…”
Section: Discussionmentioning
confidence: 99%